PSYCHOLOGICAL STUDY OF AGE CRISES IN CHILDREN’S DEVELOPMENT - Soltanova İsbandiyarova, Qamza (Health and Society, 2024)
The article examines age crises that manifest themselves in children’s mental development. The study showed that one of the criteria for the successful course of the crisis and cognitive development, in general, is the ratio of negative and constructive symptoms. Correlation analysis also revealed some relationships between the psychological characteristics of the crisis and indicators of readiness to learn. The research showed that the obtained data are not unambiguous. Greater expression of adult behaviour corresponds to higher levels of visual linear thinking (p < 0.01) and visual-motor coordination, the ability to move correctly (p < 0.05). Argument is also positively related to imaginative thinking (p < 0.05). The higher the child’s cognitive motivation and ability to concentrate, the more general questions and new topics he has in communication (p